Hubungan Pengetahuan Dan Sikap Guru Serta Pegawai Terhadap Penerapan Kawasan Tanpa Rokok - Hygea Putri Novanta; Tukiman (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Smoke-Free Areas (Kawasan Tanpa Rokok/KTR) are public health policies aimed at creating tobacco-free environments, especially in educational institutions. This study aimed to analyze the relationship between knowledge, attitudes, and individual characteristics of teachers and staff with the implementation of KTR in public senior high schools (SMA) in Binjai City. A cross-sectional quantitative design was applied with 84 respondents selected using stratified random sampling. Data were collected through questionnaires and analyzed using the chi-square test (α = 0.05). The results showed that most respondents had moderate levels of knowledge and attitude, with the majority (46.4%) also demonstrating moderate KTR-related actions. No significant association was found between age (p = 0.986), gender (p = 0.199), occupation (p = 0.526), or knowledge (p = 0.311) and KTR-related behavior. However, a significant relationship was found between smoking status (p = 0.006) and attitude (p = 0.039) with KTR implementation. Interestingly, even among those with positive attitudes, not all translated this into supportive behavior, indicating a gap between attitude and action. These findings suggest that KTR policy effectiveness in schools requires not only awareness but also institutional interventions, such as integrating KTR rules into school regulations, establishing participatory monitoring systems, and empo wering teachers and students as change agents.